Evaluation of vitamin D receptor (VDR) gene polymorphisms (FokI, TaqI and ApaI) in a family with dentinogenesis imperfecta - (:unkn) unknown (ALLERTON PRESS INC, 2013)
Dentinogenesis imperfecta Type II (DGI-II) is a condition inherited as an autosomal dominant trait and characterized by abnormal dentine structure affecting both the primary and secondary dentitions. The genetic etiology of the disease still remains unclear, suggesting a genetically heterogeneous background. The aim of this study is to manifest briefly DGI-II and to investigate the association between BsmI, TaqI and FokI polymorphisms of vitamin D receptor (VDR) gene and dentinogenesis imperfecta type II in a Turkish family by PCR-RFLP methodology. The affected mother and her two affected daughters were bb for BsmI polymorphism, whereas her unaffected son and her husband were Bb for the same polymorphism. One of the affected children was tt, the rest of the family were Tt for TaqI polymorphism, and all of the enrolled subjects were FF for FokI polymorphism. As a conclusion, BsmI polymorphism bb seems to be associated with (DGI-II), but should be examined in larger numbers in order to be considered as a risk factor.
Keywords: dentinogenesis imperfecta; vitamin D receptor gene; polymorphism; DENTIN; MUTATION; DISEASE